An assessment of teachers utilization of secondary school resource centres for teaching and learning in the state of Selangor Darul Ehsan / Nornai'lah Abdul Latiff - Abdul Latiff, Nornai'lah (2007)
The objective of the study is to assess the pattern and extent of SRC use among teachers in secondary schools in Selangor Darul Ehsan, Malaysia. The study focus on the frequency and level of use of SRC resources, services, space and facilities for teaching and learning. In addition, this study attempted to relate the teachers' knowledge of teaching and learning concept specifically resource-based learning, information literacy, collaborative teaching and lifelong learning with SRC use. The study probe further in identifying the constraints and teachers' participation in SRC programmes, teachers' expectation of teacher-librarians and motivation factors that contribute to the use of SRC. This study used a survey method involving 1366 teachers from 162 secondary schools. The questionnaires were distributed to teachers and data were tabulated and analysed using appropriate statistical tools. The findings of this study provide an overall picture of the pattern of use by teachers. Majority (68%) of the teacher's use the SRC. The level of use is still at minimal level where majority of the teachers use SRC once or twice per week. The teaching and learning activities that require very highly use of SRC are preparing, selecting and using appropriate resources. The use of print resources is at high level for both fiction and non-fiction books. The overall use of reference material is at medium level. The overall use of both periodical and journal is also at very high level. The use of Educational Television (ETV) and ASTRO Educational Channel is found to be at low level or below 40%. The overall pattern of use of SRC services showed a mixed pattern. Services with highly use are circulation, reading activities and promotion, reference and information service, while other services remain medium and low use. The overall use of space and facilities showed uneven pattern of use, where some are not heavily used and some are highly used. The space that is highly use are open reading space and reference space. Hardware facilities are used most by the teacher. Teachers are generally involved and participated in SRC programmes and activities especially in developing and sustaining students reading habit. The main factors that can motivate teachers to use SRC are the teacher-librarians having three capabilities in terms of expertise, knowledge and competencies in managing SRC.